2020
DOI: 10.1186/s12882-020-02047-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dialysis-treated end-stage renal disease patients in Kazakhstan: data from nationwide large-scale registry 2014–2018

Abstract: Background The epidemiology of dialysis patients has been little studied in developing countries and economies in transition. We examined the prevalence, incidence and mortality rate of dialysis patients in Kazakhstan, via aggregation and utilization of large-scale administrative healthcare data. Methods The registry data of 8898 patients receiving dialysis therapy between 2014 and 2018 years were extracted from the Unified National Electronic Health System (UNEHS) and linked with the national population reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Poisons and toxins cross the dialysis membrane into the dialysate, which discards the harmful substances, and then the blood is returned to the patient [ 9 ]. The number of end-stage renal disease patients requiring hemodialysis is increasing steadily over the last decades [ 10 , 11 ]. Although renal transplantation offers improved quality of life and increases survival rate compared to hemodialysis, hemodialysis is still the choice of renal replacement therapy for end-stage renal disease patients in low-income countries such as Somalia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poisons and toxins cross the dialysis membrane into the dialysate, which discards the harmful substances, and then the blood is returned to the patient [ 9 ]. The number of end-stage renal disease patients requiring hemodialysis is increasing steadily over the last decades [ 10 , 11 ]. Although renal transplantation offers improved quality of life and increases survival rate compared to hemodialysis, hemodialysis is still the choice of renal replacement therapy for end-stage renal disease patients in low-income countries such as Somalia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [ 6 ], we reported the epidemiology of dialysis-treated ESKD in Kazakhstan for the period of 2014–2018 years using big data from the Unified National Electronic Healthcare System (UNEHS) [ 7 ]; however, in-depth epidemiology of CKD over the country has never been studied. Forecasting the future trend of CKD for the next 10 years and being prepared for expected CKD cases with appropriate preventive measures are very important.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the literature shows a significant increase in the prevalence and incidence of ESRD on dialysis in Kazakhstan in 2014-2018 [5]. Despite this increase, there is a dearth of epidemiological data on ESRD within Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Even though chronic haemodialysis treatment has been available since 1974, the majority of public dialysis facilities are concentrated in large cities only, leaving access to the rural population difficult. However, legislative changes made in the early 2000s enabled the development of private dialysis centres across the nation, improving patient access to these facilities [5]. Will this alone be enough to rectify the core issue within the country with regards to dialysis to the pediatric population?…”
Section: Introductionmentioning
confidence: 99%